State and Trends of the Carbon Market 2009 - Capoor, Karan; Ambrosi, Philippe (World Bank, Washington, DC, 2013)
Over the past year, the global economy has cooled significantly, a far cry from the boom just a year ago in various countries and across markets. At the same time, the scientific community communicated the heightened urgency of taking action on climate change. Policymakers at national, regional, and international levels have put forward proposals to respond to the climate challenge. The most concrete of these is the adopted European Union (EU) climate and energy package (20 percent below 1990 levels by 2020), which guarantees a level of carbon market continuity beyond 2012. The EU package, along with proposals from the U.S. and Australia, tries to address the key issues of ambition, flexibility, scope, and competitiveness. Taken together, the proposals tabled by the major industrialized countries do not match the aggregate level of annex one ambition called for by the Intergovernmental Panel on Climate Change, or IPCC (25-40 percent reductions below 1990). Setting targets in line with the science will send the right market signal to stimulate greater cooperation with developing countries to scale up mitigation.